2007
DOI: 10.1073/pnas.0705162104
|View full text |Cite
|
Sign up to set email alerts
|

von Hippel–Lindau binding protein 1-mediated degradation of integrase affects HIV-1 gene expression at a postintegration step

Abstract: HIV-1 integrase, the viral enzyme responsible for provirus integration into the host genome, can be actively degraded by the ubiquitin-proteasome pathway. Here, we identify von HippelLindau binding protein 1(VBP1), a subunit of the prefoldin chaperone, as an integrase cellular binding protein that bridges interaction between integrase and the cullin2 (Cul2)-based von Hippel-Lindau (VHL) ubiquitin ligase. We demonstrate that VBP1 and Cul2/VHL are required for proper HIV-1 expression at a step between integrase-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 49 publications
4
93
0
Order By: Relevance
“…These findings show that oligomeric A␤ accumulation within neuronal cell bodies has pathological consequences, as proteasome impairment led to the build-up of tau protein. Another study, by Mousnier and colleagues, reported a possible prefolding-mediated proteasomal protein-degradation pathway [125]. This suggests that A␤ oligomers-prefolding complex could cause proteasome dysfunction and subsequent cell death.…”
Section: Intracellular A␤ Oligomer Toxicitymentioning
confidence: 97%
“…These findings show that oligomeric A␤ accumulation within neuronal cell bodies has pathological consequences, as proteasome impairment led to the build-up of tau protein. Another study, by Mousnier and colleagues, reported a possible prefolding-mediated proteasomal protein-degradation pathway [125]. This suggests that A␤ oligomers-prefolding complex could cause proteasome dysfunction and subsequent cell death.…”
Section: Intracellular A␤ Oligomer Toxicitymentioning
confidence: 97%
“…hydrophobic ␤-sheets) cannot easily be changed into nontoxic forms, prefoldin probably transfers them to CCT or other appropriate chaperones. Prefoldin might also deliver misfolded toxic species to the proteasome for degradation through direct interaction (38,46).…”
Section: ϫ5mentioning
confidence: 99%
“…Establishing a clear connection between the latter effect, the INstabilizing effect of p75, and the viral cofactor role requires further investigation. In addition, a cellular protein, von Hippel Lindau binding protein 1 (VBP1), has recently been suggested to foster transition of the nascently integrated PIC to transcriptional competence by facilitating IN degradation [148]. Whether and how VBP1-mediated IN degradation intersects with p75 protection of IN [78] or with the post-strand transfer gap repair step are unknown.…”
Section: P75 and Integrase Protein Degradation In Cellsmentioning
confidence: 99%